High impact practices in higher education : international perspectives - Sengupta, Enakshi (Innovations in higher education teaching and learning ;, 2023)
Universities are grappling with the issue of broadening the knowledgebases of their students to achieve excellence in education through the development and enhancement of intellectual power and capacities, preparing students to shoulder their civil and ethical responsibilities through a sense of personal growth and self-direction that can have real impact. Yet the demand for high impact practices in education is in a constant state of flux due to the ever-evolving reality of today's interconnected world. How can universities develop realistic opportunities through high impact learning and what can be the expected outcome of such learning? Collating various case studies, policies and other empirical research, High Impact Practices in Higher Education: International Perspectives examines effective high impact learning practices and demonstrates approaches that promote learning communities and common intellectual experiences. Contributors consider theoretical frameworks as well as applied models in terms of benefits gained and challenges encountered for the sake of educators, faculty members and students. With relevance for every area and discipline within higher education, High Impact Practices in Higher Education: International Perspectives facilitates the advice and support a university may need in its journey towards becoming a progressive, high impact institution.